(3GdYhGUe hGdbhGUes - (3eMeO Hf EHQGgje Hf Ydj Hf GdeQJVj Hf GdeaVd GdMSfj GdbGSej, CHh YHO Gddg, YR GdOjf, ef Bd GdhRjQ,J (B840 (3g` s
(3ChdgG (B:s
(3Gdhge GdMGOi hGdKdGhf bGd Efge jbhdhf HCjGe GdaQGYfI HWGYGJ GdCfHjGA hJhge Cf gPG jeVi hGddg GdeSJYGf hbO eQ GdLhGH Ydjg ai eSCdI GdefGhdjf s
(3BNQgG (B:s
(3aef CQGO GdTaGA GdJGe ai gPG GdeYfi aYdjg HeWGdYJg deG ajg ef JOHQ cJGH Gddg hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds